Consumption of fruits, vegetables and fruit juices and differentiated thyroid carcinoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Issue 3 (24th July 2017) - Zamora‐Ros, Raul; Béraud, Virginie; Franceschi, Silvia; Cayssials, Valerie; Tsilidis, Konstantinos K.; Boutron‐Ruault, Marie‐Christine; Weiderpass, Elisabete; Overvad, Kim; Tjønneland, Anne; Eriksen, Anne K.; Bonnet, Fabrice; Affret, Aurélie; et al.
Abstract : Fruit and vegetable (F&V) intake is considered as probably protective against overall cancer risk, but results in previous studies are not consistent for thyroid cancer (TC). The purpose of this study is to examine the association between the consumption of fruits, vegetables, fruit juices and differentiated thyroid cancer risk within the European Prospective Investigation into Cancer and Nutrition (EPIC) study. The EPIC study is a cohort including over half a million participants, recruited between 1991 and 2000. During a mean follow‐up of 14 years, 748 incident first primary differentiated TC cases were identified. F&V and fruit juice intakes were assessed through validated country‐specific dietary questionnaires. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression models adjusted for potential confounding factors. Comparing the highest versus lowest quartile of intake, differentiated TC risk was not associated with intakes of total F&V (HR: 0.89; 95% CI: 0.68–1.15; p ‐trend = 0.44), vegetables (HR: 0.89; 95% CI: 0.69–1.14; p ‐trend = 0.56), or fruit (HR: 1.00; 95% CI: 0.79–1.26; p ‐trend = 0.64). No significant association was observed with any individual type of vegetable or fruit. However, there was a positive borderline trend with fruit juice intake (HR: 1.23; 95% CI: 0.98–1.53; p ‐trend = 0.06). This study did not find any significant association between F&V intakes and differentiated TC risk; however a positive trend with fruit juice intake was observed, possibly related to its high sugar content. Abstract : What's new? The message is ubiquitous: to stay healthy, eat a diet rich in fruits and vegetables. But some cancers remain undeterred by a colorful diet. In this paper, the authors sought an association between thyroid cancer risk and consumption of fruit and vegetables. They used data from the EPIC cohort, which includes over half a million individuals with a wide range of dietary habits. Their analysis revealed no difference in risk attributable to total fruit and vegetable consumption, or consumption of any individual fruit or vegetable.